Spatial serosurvey of anti-Toxoplasma gondii antibodies in individuals with animal hoarding disorder and their dogs in Southern Brazil - Cunha, Graziela Ribeiro da; Pellizzaro, Maysa; Martins, Camila Marinelli; Rocha, Suzana Maria; Yamakawa, Ana Carolina [UNESP]; Silva, Evelyn Cristine da [UNESP]; Santos, Andrea Pires dos; Morikawa, Vivien Midori; Langoni, Helio [UNESP]; Biondo, Alexander Welker (Public Library Science, 2020)
Despite vulnerability and unsanitary conditions of animal hoarding may predispose environmental contamination and spread of vectors and pathogens, no study to date has focused on their impact on public health and zoonotic diseases. Accordingly, this study aimed to assess the seroprevalence of anti-Toxoplasma gondii antibodies and associated factors in individuals with animal hoarding disorder (AHD) and their dogs in Curitiba, Southern Brazil. Blood samples were obtained from 264 dogs (21 households) and 19 individuals with AHD (11 households). Their blood was tested by indirect fluorescent antibody test (IFAT). Overall, anti-Toxoplasma gondii seropositivity was found in 21/264 dogs (7.95%; 95% CI: 4.69-11.22) with titers ranging from 16 to 4096, and in 7/19 individuals with AHD (36.84%; CI: 15.15-58.53) with titers ranging from 16 to 64. Serological analysis for anti-T. gondii antibodies were considered positive in at least one individual or dog in 9/11 (81.82%; 95% CI: 59.03-100.00) cases that were thoroughly assessed. Surprisingly, the seropositivity of individuals with AHD and their dogs was among the lowest reportedly observed in human and dog populations of Brazil. There was no significant association between positive owners and positive dogs or the presence of cats in the household. Regard epidemiological variables, a significant association was found between dog's seropositivity and the type of dog food. To the authors' knowledge, the present study represents the first investigation of T. gondii seroprevalence in individuals with hoarding disorder and their dogs. In conclusion, despite low sanitary conditions, anti-Toxoplasma gondii antibodies frequency in individuals with AHD and their dogs are lower than the general population likely due to low protozoan load in such isolated households.